Enhanced photothermal stability of in situ grown FAPbBr3 nanocrystals in polyvinylidene fluoride by incorporation of Cd2+ ions. Issue 46 (16th November 2022) - Liu, Jizhong; Fu, Hui; Du, Zhentao; Ou, Deliu; Li, Shixian; Chen, Qiaochu; Yang, Weiyou; Zhao, Jialong; Zheng, Jinju
Abstract : We report the enhanced photothermal stability of in situ grown FAPbBr3 perovskite nanocrystals in polyvinylidene fluoride by incorporation of Cd 2+ ions, which have potential applications in backlight devices. Abstract : The photothermal stability against light irradiation and high temperature of organic–inorganic hybrid perovskite nanocrystals (PNCs) is critically important for their applications in photoelectronic nanodevices. In the present work, we report the significantly enhanced photothermal stability of FAPbBr3 PNCs, which are fabricated by in situ growth of PNCs in polyvinylidene fluoride films (FAPbBr3 @PVDF) with incorporation of Cd 2+ ions. It is found that the introduced Cd 2+ ions could effectively passivate the PNC defects and shorten the length of Pb–Br bonds, giving rise to the intensified interaction between Pb 2+ and Br − in the [PbBr6 ] 4− octahedron, which thereby suppresses the halogen ion migration under light irradiation and high temperature with enhanced photothermal stability. As a result, the Cd 2+ -doped FAPbBr3 @PVDF film exhibits durable photothermal stability with 96% and 97% photoluminescence quantum yield (PLQY) retentions, under continuous blue-light irradiation (460 nm, 13 mW cm −2 ) for over 360 h, and under both a high temperature of 333 K and blue-light irradiation over 48 h, respectively. Furthermore, the as-constructed white light-emitting-diodes (WLEDs) deliver a wide color gamut (117% of NTSC standard) with chromaticity coordinates of (0.331, 0.337), verifying their promising applications in backlight sources.